Strengthening the Values of Islamic Religious Educators in the Diversity of Inter-Tribal Relations in the Mining Ring Area Study in Central Halmahera (Eurasian Journal of Humanities and Social Sciences, 2026)
This study aims to examine the strengthening of the values of Islamic Religious Education (PAI) in the framework of the diversity of inter-ethnic relations in the mining ring area of Central Halmahera Regency. The presence of the mining industry has triggered considerable demographic changes, marked by the influx of migrant workers from various ethnicities, such as Buton, Bugis, Javanese, and Sumatra, thus potentially causing social tensions between groups. With a qualitative approach through in-depth interviews, field observations, and documentation studies, this study involved informants consisting of religious leaders, traditional leaders, village government officials, local communities, and migrant workers. The findings of the study show that the values of PAI, including ukhuwah Islamiyah (brotherhood), tasamuh (tolerance), husnudzon (good prejudice), ta'awun (helphelp), and ishlah (peace), have been internalized into a social practice that lives in the community. The mosque plays a role as a center for egalitarian social integration, where regional and tribal barriers are dissolved through the implementation of congregational worship, yasinan activities, and collective community service. This research also reveals that the strengthening of PAI values does not take place alone, but is strengthened through synergy with local Fagogoru wisdom, such asAdmit to Feeling Like a Man(Burdening each other),Courtesy re Yours(glorify each other), andBudi re Language(communicate politely), which is in harmony with the teachings of Islam. RitualCokaibaIt is clear evidence of acculturation between customs and religion as a means of da'wah as well as a tool for unifying culture. The village government also took part by implementing the Village Regulation (Perdes) on the prohibition of liquor and curfew restrictions as a form of social control based on religious values. The results of observations in the field show that there is an integrated settlement pattern without separation based on ethnicity, coffee shops function as the main public spaces for cross-cultural interactions, and help-help practices involving various tribes. These findings are corroborated by Émile Durkheim's theory of collective consciousness, John W. Berry's theory of acculturation, and Talcott Parsons' view of structural functionalism. Thus, social integration in the mining ring area does not occur by itself, but is formed through collaboration between local cultural values, religious solidarity, and various social mechanisms that have been institutionalized in the life of the people of Central Halmahera